2021
DOI: 10.1016/j.jbc.2021.101182
|View full text |Cite
|
Sign up to set email alerts
|

A peptide CORO1C-47aa encoded by the circular noncoding RNA circ-0000437 functions as a negative regulator in endometrium tumor angiogenesis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…Recently, several research groups have shown that circRNAs are capable of encoding polypeptides that serve as scaffolds for certain proteins to exert their regulatory effects ( Li et al, 2021 ; Liu et al, 2021 ; Shen et al, 2021 ). We examined the protein coding potential of the bone fide polypeptides of circ0007360 and found that the coding probabilities of them are rather low (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several research groups have shown that circRNAs are capable of encoding polypeptides that serve as scaffolds for certain proteins to exert their regulatory effects ( Li et al, 2021 ; Liu et al, 2021 ; Shen et al, 2021 ). We examined the protein coding potential of the bone fide polypeptides of circ0007360 and found that the coding probabilities of them are rather low (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our data were similar to this previous study. VEGF was confirmed to be a crucial mediator in angiogenesis [ 31 , 32 ]. Thereby, the similar function between VEGF and Rab7 might result in the similarity between our research and Wang CG et al…”
Section: Discussionmentioning
confidence: 99%
“…Results also show that CORO1C47aa is directly bound to ARNT through the PAS-B domain and involved in blocking the association between ARNT and TACC3, which led to a reduced expression of VEGF and angiogenesis. The antitumor effects of CORO1C-47aa on endometrial cancer progression suggest that CORO1C-47aa has a potential role in anti-carcinoma treatment (110).…”
Section: Translation Of Circ-0000437 In Endometrial Cancermentioning
confidence: 99%